Expert System for Diagnosing Spine Diseases Using the Forward Chaining Method - Iskandar, Iskandar; Siahaan, Muhammad Donni Lesmana; Wahyuni, Sri; Panjaitan, Dewi Afriana (International Conference on Sciences Development and Technology, 2023)
An expert system is a technology that is able to integrate medical knowledge and data processing to diagnose spinal cord diseases. With various algorithms and a carefully structured knowledge base, this expert system can identify spinal cord diseases based on the symptoms presented by the patient. The main advantage of this expert system is its ability to process data quickly and provide diagnostic recommendations consistently. The results provided from this research are an expert system for identifying spinal cord disease which was built using the Visual Basic software application system. From patient data and symptom data applied to the expert system for in spinal cord disease, it is known that the accuracy of the system for diagnosing spinal cord disease is 95% of patients.